Treinamento em habilidades sociais educativas para pais de crianças em trajetória de risco - Pinheiro, Maria Isabel dos Santos (Universidade Federal de São Carlos, 2006)
The increasing rate of aggressiveness in childhood and adolescence has mobilized investments and research in search for a solution to this concern of the society at present. The related literature appoints parental educative practices as factors that contribute towards the risk and concealment of disorders of children s behavior. The parent training programs have shown themselves as a successful alternative in the treatment of behavior disorders in childhood. The purpose of this study was to adapt a parent training program with focus on Social Educative Skills of parents and evaluate its effects on the behavior of the children. The program was structured in nine weekly group sessions, lasting 90 minutes, held in a municipal school of Belo Horizonte, Brazil. Eight mother/child dyads have participated in the program and the infants mean age was 9.38 years (sd = 2.87), where 75% of which were male. The mothers behavior was randomly evaluated prior to and after the training process by using the Social Skills Inventory and video tapes, and the children s behavior was evaluated by using the Home Situations Questionnaire and the Disruptive Behavior Inventory. The data were analyzed as to statistical and clinical significance. The results suggest that there was a reduction in the frequency and seriousness of behavior problems in most children. Application of the Parent Training Program in a larger scale shall allow validating it for treatment of children s behavior problems in similar communities.
Keywords: Estudantes em desvantagens sociais; Treinamento em habilidades sociais; Treinamento de pais; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL